2018
DOI: 10.1016/j.enbuild.2018.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Design and experiment of thermoelectric asphalt pavements with power-generation and temperature-reduction functions

Abstract: Asphalt pavements tend to absorb solar energy and accumulate heat, which results in several negative effects. They contribute to the urban heat-island effect, plastic deformation of pavements, and aging of asphalt materials. One solution is to convert or transfer the pavement heat. A brand new road thermoelectric generator system (RTEGS) is designed for this purpose. The system added three modules to the traditional asphalt pavement structure: heat-conduction, thermoelectric-conversion, and cold-end cooling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Similar works on TEG systems for pavement energy harvesting were reported by Yu et al, Kim et al, Jiang et al, and Lee et al Ortega performed FEM simulations to optimize the shape of TEG system on an asphalt pavement with the objective of maximizing the thermal gradient. Very recently, Jiang et al developed an improved TEG system, which comprised modules of heat‐conduction, thermoelectric‐conversion, and cold‐end cooling. On‐site testing for 6 months revealed that the system could reduce the pavement surface temperature by 8°C to 9°C in hot seasons, and the electrical power generated from an asphalt pavement of size 300 mm × 300 mm × 100 mm was 3300 kWh/km 2 in a single day in summer.…”
Section: Technologies Of Energy Harvesting From Pavements and Roadwaysmentioning
confidence: 99%
“…Similar works on TEG systems for pavement energy harvesting were reported by Yu et al, Kim et al, Jiang et al, and Lee et al Ortega performed FEM simulations to optimize the shape of TEG system on an asphalt pavement with the objective of maximizing the thermal gradient. Very recently, Jiang et al developed an improved TEG system, which comprised modules of heat‐conduction, thermoelectric‐conversion, and cold‐end cooling. On‐site testing for 6 months revealed that the system could reduce the pavement surface temperature by 8°C to 9°C in hot seasons, and the electrical power generated from an asphalt pavement of size 300 mm × 300 mm × 100 mm was 3300 kWh/km 2 in a single day in summer.…”
Section: Technologies Of Energy Harvesting From Pavements and Roadwaysmentioning
confidence: 99%
“…The decreasing efficiency of solar panels after abrasion by vehicles and accumulation of dust should be addressed, along with riding comfort, skid resistance, and reparability [123]. Currently, the use of temperature gradient-based thermoelectric pavement technology is limited by its low power-generating efficiency [125,144,145].…”
Section: Energy Harvesting Pavement Materialsmentioning
confidence: 99%
“…Bitumen pavement has been extensively employed in China, in view of its excellent properties such as low noise and good driving comfort [1]. In response to pavement distresses caused by the increasing traffic volume, loads, and other factors in early service conditions, virgin bitumen is usually required to be modified [2].…”
Section: Introductionmentioning
confidence: 99%